Ответы и объяснения

2014-01-16T21:23:19+04:00
Cos(2x- \frac{ \pi }{3} )=-1
cos2x-cos \frac{ \pi }{3} =-1
cos²x-sin²x- \frac{1}{2} =-1
cos²x-sin²x- \frac{1}{2} +sin²x+cos²x=0
2cos²x- \frac{1}{2} =0
2cos²x= \frac{1}{2}
cos²x= \frac{1}{4}
cosx=+- \sqrt{ \frac{1}{4} }
cosx=+- \frac{1}{2}
cosx₁= \frac{1}{2}
x₁=+-arccos \frac{1}{2} +2 \pi k, k ∈ Z
x₁=+- \frac{ \pi }{3} +2 \pi k, k∈ Z
cosx₂=- \frac{1}{2}
x₂=+-arccos(- \frac{1}{2} )+2 \pi k, k∈ Z
x₂=+- \frac{2 \pi }{3} +2 \pi k, k∈Z
Ответ: +- \frac{ \pi }{3} +2 \pi k; +- \frac{2 \pi }{3} +2 \pi k, k∈ Z